Prenatal exposure to glycol ethers and sex steroid hormones at birth. (April 2018) - Warembourg, Charline; Binter, Anne-Claire; Giton, Frank; Fiet, Jean; Labat, Laurence; Monfort, Christine; Chevrier, Cécile; Multigner, Luc; Cordier, Sylvaine; Garlantézec, Ronan
Abstract: Background: Glycol ethers (GEs) are oxygenated solvents widely found in occupational and consumer water-based products. Some of them are well-known reproductive and developmental toxicants. Objectives: To study the variations in circulating sex steroid hormones, measured in cord blood, according to biomarkers of prenatal GE exposure. Methods: The study population comes from the PELAGIE mother–child cohort, which enrolled pregnant women from Brittany (France, 2002–2006). Maternal urine samples were collected from a random subcohort ( n  = 338) before 19 weeks' gestation, from which we measured 8 alkoxycarboxylic metabolites of GEs. We subsequently measured 13 sex steroid hormones and sex hormone-binding globulin (SHBG) in cord blood samples. Linear regressions adjusted for potential confounders were used, and nonlinear dose-response associations were investigated. Results: The detection rates of GE metabolites ranged from 4% to 98%; only the 5 most detected (>20%) metabolites were investigated further. Phenoxyacetic acid (detection rate > 95%) was associated with lower levels of SHBG and various steroids (17-alpha-hydroxy-Pregnenolone, delta-5-androstenediol, and dehydroepiandrosterone) among boys and higher SHBG and 16-alpha-hydroxy-dehydroepiandrosterone levels among girls. The two other highly detected metabolites, methoxyetoxyacetic acid and butoxyacetic acid, were associated with variations in estradiol. Butoxyacetic acid was associated with higher delta-5-androstenediol levels while detectable levels of methoxyacetic acid were associated with lower levels of this hormone. Conclusion: Our study suggests that prenatal exposure to GE may affect endocrine response patterns, estimated by determining blood levels of sex steroid hormones in newborns. These results raise questions about the potential role of these changes in the pathways between prenatal GE exposure and previously reported adverse developmental outcomes, including impaired neurocognitive performance. Highlights: Several glycol ethers (GEs) are known reproductive and developmental toxicant. GEs are solvent widely used in various products including in paints, cleaning agents and cosmetics. Several circulating sex steroid hormones vary at birth with prenatal GE exposure. The delta-5 pathway seems impaired in boys with higher exposure to phenoxyethanol. These findings raise questions about the consequences of these hormonal variations.